EVALUASI PENGOPERASIAN TERMINAL BATUBULAN, GIANYAR-BALI - Adi Suar Candra; Ida Bagus Made Parsa; I Dewa Ketut Adi Pradnyana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
Transportation is about the the action of transporting someone or something from one place to another in certain time using the vehicle that move by human, animal or machine. Regarding to secure this flow of transportation going smoothly, there is a place called station on the meeting point of the interchange at one region to another. There are a couple of station in Indonesia that built and success operated. But there are at couple region, the station had some problem in their operational system. One of the Station for example is Batubulan Station in Gianyar. Batubulan Station nowdays looks abandoned by the passangers. Plus, the Station area changed into market at night time.The purpose of this research are to identify the existing condition of Batubulan Station and also to describe the factors that cause of it function change. This research done by using qualitative approach method. The technique of sample assemble for finding the interviewees in this research using purposive sampling method. Method and analysis technique used in this research is descriptive and evaluative analysis. Based on this research we found that (1) facilities uncompatibility at Batubulan Station based on the Law, so it needed to do some renovations and renewing some facilities. (2) the need of cooperation from all stakeholders to strengthen the operational system of Batubulan Station.